PERGESERAN TRADISI MANYAMBAU DI KENEGERIAN ROKAN KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Nurhasanah, Nurhasanah; Isjoni, Isjoni; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Manyambau Tradition is an accompaniment or parade activity carried out by ninik mamak and kemenakan from a place to a certain place which is usually held by the Chaniago tribe community in Kenegerian Rokan Kecamatan Rokan IV Koto Kabupaten Rokan Hulu. The purpose of this study is (1) To find out the process of carrying out the scolding activities in Kenegerian Rokan Sub-District Rokan IV Koto Rokan Hulu District . (2) To find out the function of the activities of Swarming the community in Kenegerian Rokan Sub-District Rokan IV Koto Rokan Hulu Dictrict. (3) To find out what values are contained in the activities of Swarming in Kenegerian Rokan Sub-District Rokan IV Koto Rokan Hulu District. (4) To find out what shifts occur in the activities of Screaming in Kenegerian Rokan Sub-District Rokan IV Koto Rokan Hulu District. (5) To find out the causes of changes in values, functions, and procedures in the activities of Screaming in Kenegerian Rokan Sub-District Rokan IV Koto Rokan Hulu District . The research method used in this study is a qualitative method. The results of the general research, namely shift-shifts found in the tradition of sapping, are shifts in function and shifts in the types of food served and the factors that cause shifts in the tradition of whipping are the times and technology and social systems.Key Words: Tradition, Manyambau, Kenegerian Rokan IV Koto